If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3 * 7x + 3 = 0 Multiply 3 * 7 7x + 21x + 3 = 0 Reorder the terms: 3 + 7x + 21x = 0 Combine like terms: 7x + 21x = 28x 3 + 28x = 0 Solving 3 + 28x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 28x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 28x = 0 + -3 28x = 0 + -3 Combine like terms: 0 + -3 = -3 28x = -3 Divide each side by '28'. x = -0.1071428571 Simplifying x = -0.1071428571
| 240=.03(x) | | 4f*3=8 | | -p^2+p+30=0 | | 27a-45b-9c= | | 240=x(.03)12 | | P+p^2+30=0 | | AX=D+BX-C | | 10k+5=5 | | x+(.07*x)=350 | | x+(.07*x)=300 | | 9/11x2/9 | | x+(.07*x)=250 | | 11m+30+m^2=0 | | x+(.07*x)=200 | | 6tan^2x+tanx-15=0 | | 9x^3-8=x-x^2 | | M^2+30=11m | | x+(.07*x)=150 | | 420=420x | | y+2*2=58 | | x+(.07*x)=30 | | x+(.07*x)=20 | | x+(.07*x)=15 | | x+(.07*x)=5 | | 4(x-6)+6=6(x-2)-4 | | 11-h=-10-7h | | -10x+3=0 | | 52-25-3=x+7 | | 8c-4=5c+10 | | 7-2(3x-5)=2+3(4x-7) | | 8(x+5)=6(x-2) | | 26x-6-17x+3=19x-4-10x+16 |